The Role of the Presenter (Personal Selling) in Marketing Educational Products at ABC Polytechnic of Jakarta - Bakri; SUbagiyo; Hanarti, Inna; Sudarmi, Wuly; Cletus Lamatokan, Sisca (MANAGER: Journal of Management and Administration Science, 2023)
The review means to decide the viability of personal selling in drawing in understudies during the confirmations cycle. Implementing a variety of marketing strategies, including product, pricing, promotion, and presenter strategies, is frequently necessary for the success of businesses, including educational establishments. It is believed that a key strategy for attracting prospective students is the presenter's role. The exhibition of moderators can be estimated by inspecting the proportion of candidates who come to enroll and thusly become new understudies. Maintaining a balance between registered applicants, accepted students, and incoming prospects appears to be a problem. The Jakarta ABC Polytechnic is the specific focus of the study, which is a school that focuses on training workers who are ready for work and developing human resources. The research takes a quantitative approach with the goal of describing and analyzing the role that presenters play in marketing educational products across the archipelago for professional development and educational institutions. To direct the investigation, the specialists mean to use SPSS Rendition 24, a measurable programming bundle generally utilized for information examination. SPSS can help with coordinating, breaking down, and deciphering quantitative information, permitting the scientists to reach significant determinations from their exploration discoveries.